Immobilizing Zwitterionic Molecular Brush in Functional Organic Interfacial Layers for Ultra-Stable Zn-Ion Batteries - Limeng Sun; Xianjun Cao; Li Gao; Jiayi Li; Chen Qian; Jinhu Wu; Xinming Nie; Hong Gao; Peng Huang; Yufei Zhao; Yong Wang; Jinqiang Zhang; et al. (Nano-Micro Letters)
Highlights An organic-assisted solid electrolyte interface pre-construction creates a functional organic interfacial layer (OIL-IPS@Zn) with aligned zwitterionic structures, suppressing side reactions and enhancing Zn2+ transport. OIL-IPS@Zn shows superior electrolyte affinity, enabling symmetric cells to operate stably for 3500 h at 1 mA cm−2/1 mAh cm−2 and 3200 h at 50 mA cm−2/10 mAh cm−2. With 99.90% Zn plating/stripping efficiency, full cells paired with H2V3O8 cathodes achieve over 7000 cycles.